Stunting prevention: balanced nutrition education, fill my plate, and complementary food variations for breast milk - Halimatus Sa`diyah; Ainassabih Liwani Syarafina; Dzuhri Ananda Firdaus; Mitra Dwi Murti (University of Merdeka Malang, 2024)
Optimal nutrition is very important for normal growth and the physical and intellectual development of children. One effort to maintain balanced nutrition is to use a